Immersive Technologies (AR/VR) in Science Education to Enhance Conceptual Understanding, Spatial Thinking, and Learning Engagement - Utami, Ayu Rischi (Scientica Education Journal, 2024)
This study aims to analyze the effectiveness of immersive technologies, specifically Augmented Reality (AR) and Virtual Reality (VR), in enhancing students’ conceptual understanding, spatial thinking, and learning engagement in science education. The research employed a quantitative approach using a quasi-experimental design with a non-equivalent control group. The participants consisted of an experimental group that engaged in AR/VR-based learning and a control group that received conventional instruction. Data were collected using a conceptual understanding test, a spatial thinking test, and a learning engagement questionnaire. The results showed that the experimental group achieved significantly higher post-test scores compared to the control group across all variables. The normalized gain (N-gain) analysis indicated that the experimental group reached a medium to high level of improvement, while the control group remained in the low to medium category. Statistical testing using an independent sample t-test revealed a significant difference between the two groups (p < 0.05). Furthermore, immersive technologies effectively improved students’ ability to understand abstract concepts, enhanced spatial reasoning skills, and increased learning engagement. These findings suggest that AR/VR-based learning is an effective and innovative instructional strategy for improving both cognitive and affective outcomes in science education.